Perencanaan Strategis Industri Kreatif Sektor Desain Grafis Kota Malang Aktor Pemerintah Dinas Perindustrian - Rendra Graha, Dimas Tri; Waloejo, Budi Sugiarto; Wicaksono, Agus Dwi (Jurnal Tata Kota dan Daerah, 2016)
Malang is one of Indonesia Creative City. Malang have creative industry such as design graphic as one of its creative industries prime sector. However, Design Graphic Industries development has been struggles. Survey found, Design Graphic obstruction such as design copyright violation, poor local buyer, and people perception of design. This study aims to determine how to develop design graphic. Method of development used on this study is strategic plan method. Subject planner on this study is Goverment Actor, Industrial Departement. This research finds 3 major value shift, shift of design become digital product, shift of message delivery style, and shift of people perception. Value proposition suitable use based on value shit is Costumer Intimacy. The result of strategic planning show vision that needed to take is â€œCreating Design Graphic Creative Industry orientated to costumer services with unprinted personalized designâ€. Mission used for design graphic industry is raise promotion and marketing, increase design graphic capability, develop design infrastructure, and create sustainable design bussiness climate. There are 16 action plans needed to be done by departement of industry. Action plan consist of activity such as increase marketing and promotion, consumen education, increase design graphic bussiness actor capability, develop design infrastructure and increase departement of industry capacity.Keywords: Design-Graphic-Creative-Industries, Strategic-Plan, Costumer-Intimacy, Action-Plan.